Interleukin-35 suppresses antitumor activity of circulating CD8+ T cells in osteosarcoma patients. (4th July 2019) - Liu, Ming-Xi; Liu, Qing-Yu; Liu, Ye; Cheng, Zhi-Ming; Liu, Lei; Zhang, Lei; Sun, Da-Hui
ABSTRACT: Purpose/Aim of the study : Interleukin (IL)-35 is a newly identified IL-12 cytokine family member and reveals immunosuppressive activity to CD8 + T cells in inflammation, infectious diseases, and cancers. However, little is known regarding IL-35 function in osteosarcoma. Thus, the aim of the current study was to investigate the regulatory function of IL-35 to CD8+ T cells in osteosarcoma. Materials and methods : Thirty-five osteosarcoma patients and 20 healthy individuals were enrolled. Serum CD4 + CD25 + CD127 dim/ – regulatory T cells (Tregs) and CD8 + T cells were purified. IL-35 concentration in serum and cultured supernatants was measured by enzyme-linked immunosorbent assay. Osteosarcoma cell line MG-63 cells and CD8 + T cells were stimulated with recombinant IL-35 in vitro, and modulatory function of IL-35 on these cells was assessed by investigation of cellular proliferation, cell cycle, apoptosis, and cytokine production. Results : Serum IL-35 and Treg-secreting IL-35 were significantly elevated in osteosarcoma patients. IL-35 stimulation did not affect proliferation, apoptosis, or cell cycle of MG-63 cells. Purified peripheral CD8 + T cells from osteosarcoma patients revealed dysfunctional property, which presented as decreased mRNA expressions for perforin, granzyme B, and granulysin, as well as reduced cytolytic (direct lysis of target MG-63 cells) and noncytolytic (interferon-γ and tumor necrosis factor-α production) function in coculture systems. Moreover, IL-35 stimulation further diminished cytolytic and noncytolytic activity of CD8 + T cells from osteosarcoma patients. Conclusions : The current data indicated that IL-35 contributed to CD8 + T-cell dysfunction and limited antitumor immune response in osteosarcoma.